Biologic Therapy for Psoriatic Arthritis or Moderate to Severe Plaque Psoriasis: Systematic Review with Pairwise and Network Meta-Analysis - Peruzzi, Mariangela; Colombo, Delia; Falco, Elena De; Chimenti, Isotta; Abbate, Antonio; Frati, Giacomo; Biondi-Zoccai, Giuseppe (International Journal of Statistics in Medical Research, 2014)
Background: A comprehensive assessment of the risk-benefit profile of biologic agents in psoriasis is lacking. We conducted a network meta-analysis of randomized trials on biologic agents in psoriasis. Methods: Trials on biologic agents in psoriasis (including psoriatic arthritis) were sought in several databases. Endpoints were ≥75% Reduction in the Psoriasis Area and Severity Index (PASI75), ≥20% improvement in the American College of Rheumatology core set of outcomes (ACR20), serious adverse events (SAE), and adverse events (AE) at the longest available non-cross-over follow-up. Random-effect methods were used to obtain pairwise and network pooled estimates. Results: A total of 52 trials with 17,617 patients and 9 different biologic agents included, with 52% affected by psoriatic arthritis. After an average follow-up of 18 weeks, treatment with placebo was associated with a 5.9% (5.2%-6.6%) rate of PASI75, 17.4% (15.1%-19.6%) of ACR20, 2.4% (1.9%-2.8%) of SAE, and 51.8% (50.2%-53.4%) of AE. Several biologic agents provided higher PASI75 rates than placebo, with golimumab yielding the most favorable results (relative risk [RR]=14.02 [6.85-17.11]). Accordingly, several agents provided higher ACR20 rates than placebo, with infliximab yielding the most favorable results (RR=3.02 [1.67-4.55]). Overall, rates of SAE and AE were higher for several but not all biologic agents versus placebo, with golimumab being associated with the most favorable results for SAE (RR=0.40 [0.11-1.41]), and abatacept for AE (RR=1.00 [0.79-1.22]). Conclusions: Efficacy and safety of biologic agents for psoriasis differ, and clinicians should bear in mind these features to maximize safety and efficacy in the individual patient.